Bone metastases tend to increase in non-small cell lung cancer with epidermal growth factor receptor mutation - Maleachi, Reginald; Erawati, Dini Rachma; Pratiwi, Suryanti Dwi; Andarini, Sri (Universa Medicina, 2022)
BackgroundIncreased understanding in molecular pathology of advanced non-small cell lung cancer (NSCLC) over the past decades has led to personalized treatment approaches being advocated. Epidermal growth factor receptor (EGFR) mutation that often occurs in NSCLC can be identified using immunohistochemical examinations. Moreover, clarifying the relationship between computed tomography (CT) and EGFR mutation of NSCLC might inform therapeutic decision-making. The purpose of this study was to determine the relationship between metastatic sites on primary chest CT-scan and EGFR mutation in NSCLC lung cancer patients. MethodsAn cross-sectional design using secondary data was conducted, involving 76 NSCLC patients. EGFR mutations were determined by immunohistochemical examination and metastatic sites by chest CT-scan with contrast. The collected metastatic sites comprised hilar and mediastinal lymphadenopathy, pulmonary nodules, and bone, liver, spleen and suprarenal metastases. A Chi square test was used to analyze the data. ResultsThis study revealed that the highest NSCLC stage was IVb, found in 39 samples (51.3%), while 34 (44.7%) subjects had EGFR mutation. There was no statistically significant difference between metastatic site and positive EGFR mutation, although positive bone metastases (54.8%) tend to have more numerous positive EGFR mutations compared to negative bone metastases (37.7%) (p=0.142). ConclusionsPatients with positive bone metastases tend to have higher positive EGFR mutation compared to negative bone metastases in NSCLC lung cancer patients. Prospective studies evaluating patients with EGFR mutation for bone metastases should be considered. This can provide information on therapeutic decision-making to obtain good clinical outcomes.